2011
DOI: 10.1007/s10443-011-9187-x
|View full text |Cite
|
Sign up to set email alerts
|

Fire Burnthrough Response of CFRP Aerostructures. Numerical Investigation and Experimental Verification

Abstract: Aircraft structures are designed to withstand further to dynamic mechanical loadings thermal loads too. In the event of an external fire (while the aircraft is on the ground) the fuselage structure has to withstand and delay fire penetration. Prolonged burnthrough time is the design target. In the current work, a progressive fire-degradation material model is developed that links decomposition kinetics with the thermophysical properties of polymer composite materials. The material model is then implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
(22 reference statements)
2
11
0
Order By: Relevance
“…Char was formed as a result of an epoxy and reinforced fibre decomposition and oxidisation. As more fire impinges with time, one of the composites that was hybridized with kenaf fibre burnt through at about 10 minutes 22 seconds, while the other three composites withstood the flame for 15 minutes according to the standard including the other composite hybridized with flax fibre, the result obtained was in agreement with the result in Sikoutris et al [30]. The FML composites fabricated showed good fire resistance; therefore, these composites can be used in fire designated zone of an aircraft engine since they withstood the flame temperature of about 1100 ± 80 C for the stated time according to the standard.…”
Section: Fire Behavioural Test Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Char was formed as a result of an epoxy and reinforced fibre decomposition and oxidisation. As more fire impinges with time, one of the composites that was hybridized with kenaf fibre burnt through at about 10 minutes 22 seconds, while the other three composites withstood the flame for 15 minutes according to the standard including the other composite hybridized with flax fibre, the result obtained was in agreement with the result in Sikoutris et al [30]. The FML composites fabricated showed good fire resistance; therefore, these composites can be used in fire designated zone of an aircraft engine since they withstood the flame temperature of about 1100 ± 80 C for the stated time according to the standard.…”
Section: Fire Behavioural Test Resultssupporting
confidence: 88%
“…Different devices were used to measure the flame temperature and heat flux such as those reported by Mohammed et al, [27], and convective and radiative heat transfer were also measured using different devices as reported by Balland et al, [28]. The flammability nature of some composites such as carbon reinforced epoxy was among the issues that have grabbed the attention of researchers to find the solution, whereby research on flame retardant polymers was undertaken to reduce the flammability of the composite, and also to come up with the most suitable reinforced fibres (carbon, glass and Kevlar) to be used in aircraft components [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition of epoxy is observed, which is then followed by char formation and, as the composites are further exposed to the higher temperature, the reinforced fibers react and also decomposed. This forms a char that is later oxidized, which is closely similar to the phenomenon observed in [20]. For the four composites that have been considered in this study, three of them are shown to be fireproof (CAFRALL, CARALL and CF+AA) while CAKRALL is a fire resistant composite.…”
Section: Fig 3 Fibre-metal Laminates On Fire Testsupporting
confidence: 66%
“…Polymers are generally light weight with acceptable mechanical properties but they degrade frequently under high temperature and fire propagation . Thermal stability and flame retardancy of the polymers may be improved by various techniques, particulate reinforcement is one of the famous methods .…”
Section: Introductionmentioning
confidence: 99%